Affordability of private schools: exploration of a conundrum and towards a definition of 'low-cost'. (3rd July 2016) - Tooley, James; Longfield, David
Abstract: The affordability of private education is a contentious issue. While the extent of 'low-cost' private schooling is widely accepted, there is no agreement on what 'low-cost' means in this context and how this relates to affordability for poor families. This paper addresses the lacuna in the literature by defining 'low-cost' in relation to what poor families could afford if they were to send all their children to school while restricting their expenditure on schooling to a fixed proportion of their total family expenditure. This approach links the definition of 'low-cost' to internationally accepted poverty lines. Two examples from recent research in South Sudan and Liberia illustrate the flexibility of the new method. The paper also addresses the 'conundrum' in the research literature, which suggests low-cost private schools are unaffordable for poorest families, when the same literature typically shows some of the poorest using these schools.